Interfaith dialogue - Noor, Noraini M. (Wiley-Blackwells, 2012)
Interfaith dialogue as a contemporary movement can be traced back to the decision of some churches at the beginning of the 20th century to extend cooperation and build relations with non-Christians. This initiative came from the Christian missionaries’ need to adapt to conditions of work in Asia, and the first few world missionary conferences (Edinburgh in 1910, Jerusalem in 1928, and Tambaram, India in 1938) paved the way for the initial discussions. But the Christians remained divided on how they should approach other religions...